Mapping neural auditory encoding profiles across different levels of cognitive functioning in ageing and dementia - Varjopuro, Saara (My University, 2024)
Research indicates that persons with dementia (PWDs) often experience central auditory processing dysfunction, which could potentially serve as an early indicator of the condition. Mismatch negativity (MMN) is an objective measure of memory-based central auditory processing and has been used to study cognitive decline across various clinical populations. Although its application in dementia research remains limited, it has been suggested as an index for cognitive decline in dementia. This thesis aimed to investigate the impact of cognitive functioning, ranging from healthy aging to severe dementia, on MMN responses to four deviant types (intensity, duration, location, and frequency) using the multi-feature paradigm across six regions of interest. Cognitive decline, as determined by the Montreal Cognitive Assessment Scale (MoCA), was found to have an attenuating effect on frequency and location MMN amplitudes but not intensity and duration. Furthermore, the attenuation of frequency MMN was found to be significant particularly in central and temporoparietal regions, with a more pronounced effect in central regions compared to the right temporoparietal region. Additionally, exploratory correlational analyses revealed that a background in music training was associated with more negative MMN responses for frequency and location deviants. The correlation was found to be moderate in central regions for location and more broadly for frequency. The results of this thesis support MMN as an index for cognitive decline in dementia and tentatively suggest that musical training may have some preservative effect on central auditory processing in healthy and pathologically ageing nonmusicians.
Keywords: dementia, mismatch negativity, cognitive decline, auditory encoding